Analysis of Klebsiella Pneumonia and Resistance Genes Coding and Carbapenemase Production in National Referral Hospital Wastewater - Simanjuntak, Glory Gelarich; Karuniawati, Anis; Saharman, Yulia Rosa; Muziasari, Windi (Poltekkes Kemenkes Tanjung Karang, 2023)
Hospitals, as a source of transmission and spread of bacteria carrying antibiotic-resistant genes (ARGs) as well as a high source of antibiotic compounds, are a significant reservoir of antibiotic-resistant gene transfer that causes bacteria to develop multidrug resistance (MDR). Klebsiella pneumonia is a bacterium often found in wastewater with a high level of Extended Spectrum Î²-lactamase (ESBL) and carbapenemase resistance. This study aimed to determine Klebsiella pneumonia and resistance genes encoding ESBL and carbapenemase in hospital wastewater to obtain primary Antimicrobial Resistance (AMR) data in the environment, which was first conducted in Indonesia. The resistance gene detection method was developed using High Throughput Real-Time and conventional Real-Time (HT-RT PCR). The data obtained were relative abundance and copy number. The results showed that blaTEM and blaNDM were the highest ARGs. Conventional Real-Time PCR results showed better sensitivity in detecting K. pneumoniae and ARGs than HT-RT PCR. The detection of K. pneumoniae and ARGs in RSCM wastewater in Indonesia indicates the need to improve the handling of RSCM WWTP to monitor the number of microbial resistances to antibiotics.